A novel LaIII‐based metal–organic framework (MOF) with a new topology: poly[diaquabis(μ5‐2, 5‐dioxopiperazine‐1, 4‐diacetato)(μ2‐oxalato)dilanthanum(III)]. (4th January 2013) - Chen, Wen‐Xian; Liu, Qiu‐Ping; Zhuang, Gui‐Lin; Zhou, Sheng‐Jun
<x xml:space="preserve">Abstract</x> In the title metal–organic framework (MOF), [La(C8H8N2O6)(C2O4)0.5(H2O)]n, the LaIII cation is coordinated by eight O atoms in a square antiprismatic configuration. Each LaIII cation is connected to adjacent LaIII cations by bridging 2, 5‐dioxopiperazine‐1, 4‐diacetate (PODC2−) and oxalate (lying about an inversion centre) ligands, generating two‐dimensional grid layers. The layers are further linked via the carboxylate groups of the PODC2− ligands in syn–syn and syn–anti modes, resulting in a three‐dimensional framework with a short Schläfli vertex notation of {47.63}{47.67.8}.